The Human Dimension of Open Innovation: Structured Literature Review - Galiulina, Asiya; Touate, Samira (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
The concept of open innovation was first introduced in 2003 by Henry Chesbrough. Research on this topic has been pursued, observing the subject from different angles and integrating it into different scientific fields. However, the “human side” of open innovation is still understudied; hence, there is a need to link open innovation with HRM. The aim of this paper is then to find out what has already been done in this field (the contributions of the various studies undertaken) and what remains to be achieved (perspectives for future research). To do this, a structured literature review on the subject was conducted.